Reduction of PAPR based on T-OFDM and adjacent PTS techniques
This study considers an encoding digital technique that uses Orthogonal FrequencyDivision Multiplexing(OFDM) and investigates its properties. The primary advantage of OFDM over single-carrier schemes is its ability to cope with severe channel conditions (e.g., attenuation of high frequencies in a long copper wire, narrow band interference, and frequency-selective fading caused by multipath) without complex equalization filters. The prominent features associated with OFDM have been exploited in the area of high speed communication networks. OFDM is a new and crucial modulation technique that is being developed, under the communication systems domain. The signals from OFDM can not only fight multipath propagation and fading channels but also advocate huge rates of data. Nevertheless, OFDM too has its disadvantage as it is a multicarrier system and can face issues because of the demanded summation of sinusoids during the combination of the in-phase subcarriers, which in turn tends to produce high power peaks. The performance of the BER can be degraded by the big fluctuations in the power envelope called peak to average power ratio (PAPR), which causes in-band and out-band distortion. There are a plethora of methods to solve the problem posed by the PAPR that includes Selected Mapping (SLM), Partial Transmit Sequence (PTS) and clipping of amplitude